2016
DOI: 10.1007/s12571-016-0589-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education on household food security in two informal urban settlements in Kenya: a longitudinal analysis

Abstract: Poverty and food insecurity continue to feature prominently in the global agenda, with particularly close attention being paid to the determinants of food insecurity. However, the effect of education is mixed and remains understudied in low income countries. Using longitudinal data collected between 2007 and 2012 in Kenya, we investigated the effect of household education attainment on food security among poor urban households. Household food security was constructed from a set of four key items while educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
77
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 31 publications
17
77
0
8
Order By: Relevance
“… 1–5: (Ferro‐luzzi et al, 2001; Hillbruner & Egan, 2008; Hoorweg, Foeken, & Klaver, 1995; Panter‐Brick, 1997; Trowbridge & Stetler, 1982); 6: (Endo et al, 2016); 7: (Cinner et al, 2016); 8, 9: (Geheb & Binns, 1997; Watson et al, 2013). 10: (Brashares et al, 2004); 11, 12: (de Jesus Silva, de Paula Eduardo Garavello, Nardoto, Mazzi, & Martinelli, 2016; Wilkie & Godoy, 2001); 13: (Harris‐Fry et al, 2015); 14: (Bashir et al, 2012); 15: (Baulch & McCulloch, 1998); 16: (Mutisya, Ngware, Kabiru, & Kandala, 2016); 17: (Duarte, Sampaio, & Sampaio, 2009); 18: (Machado & de Oliveira Neto, 2016). …”
Section: Introductionmentioning
confidence: 99%
“… 1–5: (Ferro‐luzzi et al, 2001; Hillbruner & Egan, 2008; Hoorweg, Foeken, & Klaver, 1995; Panter‐Brick, 1997; Trowbridge & Stetler, 1982); 6: (Endo et al, 2016); 7: (Cinner et al, 2016); 8, 9: (Geheb & Binns, 1997; Watson et al, 2013). 10: (Brashares et al, 2004); 11, 12: (de Jesus Silva, de Paula Eduardo Garavello, Nardoto, Mazzi, & Martinelli, 2016; Wilkie & Godoy, 2001); 13: (Harris‐Fry et al, 2015); 14: (Bashir et al, 2012); 15: (Baulch & McCulloch, 1998); 16: (Mutisya, Ngware, Kabiru, & Kandala, 2016); 17: (Duarte, Sampaio, & Sampaio, 2009); 18: (Machado & de Oliveira Neto, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the probability of being food secure of household decreases as age increases [42]. This may be due to the fact that as the age of household head increases, most of the productive household members may leave the household due to marriage, education, rural out-migration and the like.…”
Section: Empirical Literaturesmentioning
confidence: 98%
“…The growth of slums coupled with limited urban agriculture, suggests the urban poor population is increasingly becoming vulnerable to food insecurity (Mutisya et al, 2016). Although both rural and urban people are affected by impacts of the food crisis, the urban poor have been among the hardest hit (FAO, 2009a).…”
Section: Introductionmentioning
confidence: 99%